KEMAMPUAN LITERASI MATEMATIKA MAHASISWA DENGAN GAYA BELAJAR SEKUENSIAL DALAM MENYELESAIKAN MASALAH STATISTIKA - Khotimah, Khusnul; Nasrulloh, Muhammad Farid (STIT Pringsewu, 2018)
The purpose of this study is to describe the mathematical literacy skill in students with sequential learning styles in solving statistical problems. This research is a qualitative research. The process of collecting data in this study is done by giving a questionnaire learning style, providing problem-solving tasks, then choose one of the test results to be described. Data analysis is done by collecting data, reducing data, and verifying data. The results obtained in this study are sequential subjects have literacy skills at level 1 that is Using knowledge to solve routine problems and yet still blom can solve the problem of the general context. The sequential subject has a literacy skill at level 2 that can solve problems with formulas. sequential subjects have not been able to carry out the procedures well in solving the problem and have not been able to choose a problem-solving strategy, according to level 3. Sequential subjects simply work effectively with the model and can choose and integrate different representations, then connect it with the real world according to level 4 . Sequential subjects have literacy skills at level 5 ie Working with models for complex situations. The subject has been able to show better variation of endurance with the coefficient of variation, but has not been able to use reasoning in solving mathematical problems and can make generalizations according to level 6.